Sem corpo, sem crime:uma proposta de jogo didático, como recurso no ensino de Genética - VILLAMAR, João Vitor Neves (2023)
High school and university students see Genetics as one of the most complex disciplines in Biology, because they address complex calculations, terms and concepts and non-practical subjects, therefore, the use of didactic resources has been consolidated as a strategy to motivate and arouse interest in the contents. The objective was to produce a proposal for a didactic game, to work theoretical and practical aspects of genetics in a contextualized way with the daily life of Criminal Forensics, aiming at a better understanding and fixation of the concepts. The game is based on the board games: "Detective" (Star) along with the game "DNA Detective" by Kenneth Wallace-Müller of the Gene Jury team. The game consists of: 1 board; 8 pawns; 2 Data; 8 character cards; 11 crime scene cards; 8 weapons cards; 8 blood type cards; presentation of an incident report; 50 notebooks; 7 genetics question cards; 1 envelope; 10 crime card; destined to solve a crime. This didactic resource, based on playfulness and contextualization, can facilitate and expand the understanding of knowledge of genetic concepts, in addition to arousing interest in learning, participating in activities and promoting interaction among students. Key